A narrative pedagogy for Teacher Education - Contreras Domingo, José; Quiles-Fernández, Emma; Paredes Santín, Adrià (Márgenes, Revista de Educación de la Universidad de Málaga, 2019)
This paper focuses on our experiences as teacher educators at the Faculty of Education at the University of Barcelona. It enhances how a narrative pedagogy might be lived as an educational practice to be alongside our students and their own ways to cultivate and shape their professional knowledge. To develop a narrative awareness and knowledge does not only require attending to the stories experienced by them before they are part of our university courses (although these experiences must be present). We believe it is about cultivating a narrative thought that, as a relational one, it enables pedagogical deepening. Thinking with our own and others' stories also has allowed us to ponder about how we prepared ourselves to teach. During the process it became crucial to imagine how we three were preparing ourselves to teach and to share a narrative pedagogy with our students. This experience is related to how we cultivate a narrative knowledge and in what ways the narrative inquiry is lived as a pedagogical practice. In this sense, the paper shows a range of ways in which a narrative approach might be present in a classroom as well as a reflective note about teacher education as a space for narrative inquiry.